On Further Analogs of Hilbert's Inequality - Yongjin Li; You Qian; Bing He (International Journal of Mathematics and Mathematical Sciences)
By introducing the function |lnx−lny|/(x+y+|x−y|), we establish new inequalities similar to Hilbert's type inequality for integrals. As applications, we give its equivalent form as well.